2003
DOI: 10.1053/comp.2003.50011
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative symptoms and amnesia in Dutch concentration camp survivors

Abstract: We examined to what extent dissociative phenomena in concentration camp survivors are related to posttraumatic stress symptoms. Self-reports of amnesia for traumatic war events and other dissociative experiences were studied in a sample of 31 Dutch survivors of World War II (WWII) Japanese concentration camps. Seventeen survivors treated for war-related psychiatric symptoms were compared to 14 concentration camp survivors who had no psychiatric diagnosis. Although survivors who received treatment scored signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…Moreover, because of the substantial phenomenological overlap between PTSD and depression (e.g., Rosen & Lilienfeld, 2008), our fi ndings are also reminiscent of a recent study by Booij and Van der Does (2007), demonstrating that higher levels of cognitive reactivity are a vulnerability marker of depression. Furthermore, we obtained evidence that the tendency to dissociate is positively related to levels of post-traumatic stress symptoms, thereby lending further support to the belief that dissociation overlaps with PTSD symptomatology (e.g., Ozer et al, 2003; but see also Merckelbach, Dekkers, Wessel, & Roefs, 2003a, 2003b. Note that Ozer et al (2003) found that peritraumatic dissociation (e.g., changes in cognitive and perceptual functioning during the trauma) was among the most potent predictors of PTSD symptom severity.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, because of the substantial phenomenological overlap between PTSD and depression (e.g., Rosen & Lilienfeld, 2008), our fi ndings are also reminiscent of a recent study by Booij and Van der Does (2007), demonstrating that higher levels of cognitive reactivity are a vulnerability marker of depression. Furthermore, we obtained evidence that the tendency to dissociate is positively related to levels of post-traumatic stress symptoms, thereby lending further support to the belief that dissociation overlaps with PTSD symptomatology (e.g., Ozer et al, 2003; but see also Merckelbach, Dekkers, Wessel, & Roefs, 2003a, 2003b. Note that Ozer et al (2003) found that peritraumatic dissociation (e.g., changes in cognitive and perceptual functioning during the trauma) was among the most potent predictors of PTSD symptom severity.…”
Section: Discussionsupporting
confidence: 72%
“…der Fragmentierung der Erinnerung und der PTBS-Symptomatik kein Zusammenhang bestand. Auf der Basis von subjektiven Einschätzungen untersuchten Merckelbach et al [45] den Abruf traumatischer Erinnerungen bei niederländischen Überlebenden von japanischen Konzentrationslagern im heutigen Indonesien mit und ohne PTBS-Symptomatik. Die Ptbs-Gruppe berichtete wiederum über mehr intrusionen und häufigere Vermeidung; die beiden Gruppen unterschieden sich jedoch nicht bezüglich der Abrufbarkeit der traumatischen erinnerungen.…”
Section: Subjektive Einschätzungen/aussagevergleicheunclassified
“…This type of amnesia is termed organic amnesia . Although there are well‐documented cases of offenders who cannot recall their crime due to organic amnesia caused by a blow to the head, a sleeping disorder or temporal lobe epilepsy (for examples see Merckelbach & Christianson, 2007), this is a rare form of amnesia. There have been cases, for instance, in which defendants claim that their alcohol consumption prompted a sleepwalking episode during which they committed a crime that they cannot remember.…”
Section: Malingered Crime‐related Amnesiamentioning
confidence: 99%